Correlação entre contexto morfoestrutural e sismicidade nas regiões de João Câmara e São Rafael (RN) - Amaral, Cristiano de Andrade (2000)
This MSc thesis describes brittle deformation in two seismic zones located in north-eastern Brazil: João Câmara and São Rafael, Rio Grande do Norte State. Both areas show seismogenic faults, Samambaia and São Rafael, indicated by narrow zones of epicentres with a strike of 040o, a lenght of 30 km and 4 km, and a depth of 1-12 and 0,5-4 km, respectively. The first seismological and geological studies suggested blind faults or faults that were still in the beginning of the nucleation process. The region is under E-W-oriented compression and is underlain by Precambrian terrains, deformed by one or more orogenic cycles, which generated shear zones generally marked by strong pervasive foliation and sigmoidal shapes. The crystalline basement is capped by the Cretaceous Potiguar basin, which is also locally capped by Pliocene continental siliciclastic deposits (Barreiras Formation), and Quaternary alluvium. The main aim of this study was to map epicentral areas and find whether there are any surface geological or morphotectonic expression related to the seismogenic faults. A detailed geological map was carried out in both seismic areas in order to identify brittle structures and fault-related drainage/topographic features. Geological and morphotectonic evidence indicate that both seismogenic faults take place along dormant structures. They either cut Cenozoic rocks or show topographic expression, i.e., are related to topographic heights or depressions and straight river channels. Faults rocks in the Samambaia and São Rafael faults are cataclasite, fault breccia, fault gouge, pseudotachylyte, and quartz veins, which point to reactivation processes in different crustal levels. The age of the first Samambaia and the São Rafael faulting movement possibly ranges from late Precambrian to late Cretaceous. Both fault cut across Precambrian fabric. They also show evidence of brittle processes which took place between 4 and 12 km deep, which probably have not occurred in Cenozoic times. The findings are of great importance for regional seismic hazard. They indicate that fault zones are longer than previously suggested by seismogenic studies. According to the results, the methodology used during this thesis may also be useful in other neotectonic investigation in intraplate areas